Nonlinear dynamic response and vibration of nanocomposite multilayer organic solar cell. (15th January 2018) - Duc, Nguyen Dinh; Seung-Eock, Kim; Quan, Tran Quoc; Long, Dang Dinh; Anh, Vu Minh
Abstract: In the recent years, organic solar cell (OSC) has attracted much interest of the research community due to its great promise as renewable sources. This paper presents the first analytical approach to investigate the nonlinear dynamic response and vibration of imperfect rectangular nanocompsite multilayer organic solar cell subjected to mechanical loads using the classical plate theory. Nanocompsite organic solar cell consists of five layers of Al, P3HT:PCBM, PEDOT:PSS, IOT and glass. Motion and compatibility equations are derived using the classical plate theory and taking into account the effects of initial geometrical imperfection and geometrical nonlinearity in Von Karman – Donnell sense. The Galerkin method and fourth – order Runge – Kutta method are used to give explicit expressions of natural frequencies, nonlinear frequency – amplitude relation and nonlinear dynamic responses of nanocompsite organic solar cell. The numerical results show the influences of geometrical parameters, the thickness of layers, imperfections, and mechanical loads on the nonlinear dynamic response and nonlinear vibration of nanocompsite organic solar cell.